Tooth Multi-Sectioning with the Use of Magnification, for Extraction of a Deeply Impacted Lower Second Molar with Entrapment of the Inferior Alveolar Nerve: Report of a Case - Tilaveridis Ioannis; Dalambiras Stilianos; Lazaridou Maria; Zouloumis Lambros (Balkan Stomatological Society, 2016)
Inferior alveolar nerve injury is one of the most serious complications of mandibular molar surgery and may lead to litigation for mal-practice. Entrapment of the inferior alveolar nerve to roots of an impacted mandibular molars is extremely rare. The aim of this case report is to stress the importance of tooth multi-sectioning with the use of magnification for the safe removal of a deeply impacted second molar with entrapment of the inferior alveolar nerve in its proximal root.